O dever do sacrifício: uma reflexão sobre as motivações dos pilotos Kamikaze na Segunda Guerra Mundial - Gonçalves, Edelson Geraldo (2012)
This dissertation addresses the Kamikaze squadron, the Japanese suicide pilots in World War II. The objective of this study is to analyze the trajectory of this group in the cultural and political landscape of Imperial Japan during World War II, addressing the formation of model of government that ended up to ally with the Germans and Italians during World War, and also the ideology who led the Japanese population during this period, this ideology is sustained mainly by the ethos that was built and developed during the first half of the twentieth century: the Bushido. The members of the Kamikaze squad ended up joining the history, especially in the West as examples of fanaticism for a cause, but through the observation of sources left from testimonies like people who had to live and deal with the Kamikaze (as allies and enemies) until the words of the Kamikaze's own left by such means as letters and diaries, we will seek to understand what was the positioning of these pilots in this scenario, getting away from the stereotype, to seek to understand the current political and cultural motivations that led these pilots to accept this sacrifice nominally made by the Emperor's honor and greatness of the Empire.